The First Refinancing Of Railway Infrastructure In Indonesia: A Part of Public-Private Partnerships (PPP) - Helmi Adam; Adler Haymans Manurung; Roy Sembel; Jatmiko Murdiono (Journal of Accounting and Finance Management, 2023)
Refinancing is an activity that can generate profits for the recipient. Carrying out refinancing can be a challenge for a company so it will make efforts well and optimally so that the refinancing is successful. This research uses a case study method by collecting data through interviews and documentation studies related to refinancing by PT Celebes Railway Indonesia (CRI). The aim of this research is to describe the refinancing carried out by PT CRI with the "Makassar-Parepare Railway" project which uses the Availability Payment (AP) scheme. PT Celebes Railway Indonesia has carried out refinancing after the completion of the construction period, the operations and maintenance processes have also been carried out and the first Availability Payment has been absorbed in December 2022. Refinancing is carried out based on stages developed by PT CRI itself so that profits are obtained for the Company. PT CRI is the pioneer of the first refinancing of railway infrastructure in Indonesia. It is hoped that the success of the refinancing carried out by PT CRI can be used as a benchmark and can be used as a guide for future researchers in carrying out refinancing.